The two brothers - Khan, Saniyasnain; Anand, Achla Anand, Achal K. (Goodword Books New Delhi, 2001)
"The Two Brothers: Quran Stories for Little Hearts" is a heartwarming tale that explores the bond between two brothers and the lessons they learn about love, sacrifice, and forgiveness. Set against a backdrop of moral dilemmas, the story follows the brothers as they face challenges that test their relationship and values. Through their experiences, they come to understand the importance of empathy, cooperation, and the strength of family ties. This engaging narrative, accompanied by colorful illustrations, aims to instill important ethical lessons in young readers while highlighting the significance of compassion and understanding in resolving conflicts.